2010
DOI: 10.3945/ajcn.2009.28404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid on body fat accretion in overweight or obese children

Abstract: CLA supplementation for 7 +/- 0.5 mo decreased body fatness in 6-10-y-old children who were overweight or obese but did not improve plasma lipids or glucose and decreased HDL more than in the placebo group. Long-term investigation of the safety and efficacy of CLA supplementation in children is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 34 publications
1
69
0
6
Order By: Relevance
“…Indeed the majority of results on the anti-diabetic properties of CLA relate to studies where only fasting plasma or serum glucose or insulin have been measured, are not the main focus of the study and typically have small sample sizes. Given these limitations, it is perhaps not surprising that the overall results show no effects of CLA supplementation (56,61,62,65 -67,70,71,104,106,132,154) or consumption of CLA-enriched products (45,63,73,102,103) on glucose and insulin. However, supplementing with a CLA mixture has shown beneficial effects on insulin resistance in healthy male subjects (155) and type 2 diabetic subjects (74) .…”
Section: Conjugated Linoleic Acid Insulin Resistance and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed the majority of results on the anti-diabetic properties of CLA relate to studies where only fasting plasma or serum glucose or insulin have been measured, are not the main focus of the study and typically have small sample sizes. Given these limitations, it is perhaps not surprising that the overall results show no effects of CLA supplementation (56,61,62,65 -67,70,71,104,106,132,154) or consumption of CLA-enriched products (45,63,73,102,103) on glucose and insulin. However, supplementing with a CLA mixture has shown beneficial effects on insulin resistance in healthy male subjects (155) and type 2 diabetic subjects (74) .…”
Section: Conjugated Linoleic Acid Insulin Resistance and Diabetesmentioning
confidence: 99%
“…* Subjects exercising. (73) . However, in a few cases it has been noted that the largest reduction in BFM occurs in the lower body (for example, legs) (56,67) .…”
Section: Conjugated Linoleic Acid and Body Compositionmentioning
confidence: 99%
“…6,13,14 The results from these previous studies have been controversial, probably because the the objective of the human studies was the reduction of existing fat deposits, whereas in animals, the aim was to decrease the number of adipocytes and consequently reduce fat deposition.…”
Section: Introductionmentioning
confidence: 96%
“…Since publication of the EFSA opinions, four additional randomised controlled trials (RCTs) in humans have been reported on the effects of CLA on fasting blood glucose and insulin concentrations and on the static surrogate marker of insulin resistance HOMA-IR (Joseph et al, 2011;Pfeuffer et al, 2011;Racine et al, 2010;Sluijs et al, 2010). None of these studies had insulin sensitivity or glucose homeostasis as a primary outcome, but rather body weight and body composition (Joseph et al, 2011;Racine et al, 2010), aortic pulse wave velocity (PWV, Sluijs et al, 2010), or endothelial function (Pfeuffer et al, 2011).…”
Section: Effects On Insulin Sensitivity and Glucose Metabolismmentioning
confidence: 99%
“…None of these studies had insulin sensitivity or glucose homeostasis as a primary outcome, but rather body weight and body composition (Joseph et al, 2011;Racine et al, 2010), aortic pulse wave velocity (PWV, Sluijs et al, 2010), or endothelial function (Pfeuffer et al, 2011).…”
Section: Effects On Insulin Sensitivity and Glucose Metabolismmentioning
confidence: 99%